EFFECTIVENESS OF THE IMPLEMENTATION OF THE SOCIAL WELFARE INFORMATION SYSTEM–NEXT GENERATION (SIKS–NG) IN SINGOPADU VILLAGE, TULANGAN DISTRICT, SIDOARJO REGENCY - Kurniawati, Christanty Dwi; Choiriyah, Ilmi Usrotin (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to describe and analyze various problems in depth through field observations regarding the Effectiveness of the Implementation of the Social Welfare Information System–Next Generation (SIKS-NG) in Singopadu Village, Tulangan District, Sidoarjo Regency. Method: This study uses a qualitative method with a descriptive approach. The technique carried out by the author uses the purposive sampling method which is carried out by collecting data through observation, interviews, and documentation. Data analysis uses the Miles and Huberman model with stages of data reduction, data presentation, and conclusion drawn. Result: The results of this study using the concept of Budiani's theory, namely: first, the accuracy of the target program can be concluded that it is still not in accordance with this because there are still shortcomings, there is a discrepancy between the data in the application and the manual data owned by the Singopadu Village government. Second, the Socialization Program can be said to be inappropriate because the socialization program was not carried out due to concerns that the community would apply for assistance independently. Third, the Program Objectives in this indicator are not appropriate because the distribution of social assistance is not on target and the program is running less effectively. Fourth, Program Monitoring, that there are still shortcomings, namely the lack of supervision of the performance of SIKS-NG Operators in carrying out data updates at the village level. Novelty: This research presents a novelty in the study of the effectiveness of the implementation of SIKS-NG with a focus on specific local contexts and related socialization strategies that are counter-productive, where the village deliberately does not conduct open socialization to the community.